2021
DOI: 10.1002/aqc.3722
|View full text |Cite
|
Sign up to set email alerts
|

Effective number of breeders and reconstructed sibships reveal low reproductive output by a reintroduced population of endangered fish

Abstract: 1. Fishes with periodic life histories are long-lived, slow to mature, and have intermittent periods of successful recruitment, limiting the ability of managers to recover their populations rapidly.2. Endangered razorback sucker (Xyrauchen texanus) in the Colorado River Basin, USA, is a periodic strategist whose persistence is largely dependent on hatchery augmentation. Stocking efforts have increased population sizes in the basin; however, natural recruitment remains extremely limited. 3. Annual reproductive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Additionally, preliminary results from genetic parentage analyses of translocated razorback sucker and larvae suggest translocated fish successfully reproduced upstream of the waterfall post‐translocation (Saltzgiver, 2023). By increasing the survival of adults and providing access to spawning habitat upstream, translocation provides a means to increase reproductive rates for razorback sucker, a species experiencing reproductive and recruitment bottlenecks in the San Juan River (Diver et al, 2021). Schlosser's dynamic landscape model of stream fish population ecology conceptually links the importance of movement among patchily distributed habitats for life cycle completion and population persistence (Schlosser, 1991, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, preliminary results from genetic parentage analyses of translocated razorback sucker and larvae suggest translocated fish successfully reproduced upstream of the waterfall post‐translocation (Saltzgiver, 2023). By increasing the survival of adults and providing access to spawning habitat upstream, translocation provides a means to increase reproductive rates for razorback sucker, a species experiencing reproductive and recruitment bottlenecks in the San Juan River (Diver et al, 2021). Schlosser's dynamic landscape model of stream fish population ecology conceptually links the importance of movement among patchily distributed habitats for life cycle completion and population persistence (Schlosser, 1991, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A recent evaluation of captured larvae indicated that the number of effective breeders and the number of repeat‐spawning adult Razorback Suckers within the San Juan River were relatively low (Diver et al. 2021). Reconnecting the migratory routes of adult Razorback Suckers to spawning sites upstream of the PF Waterfall and the PNM weir could be a valuable tool for increasing reproductive output.…”
Section: Discussionmentioning
confidence: 99%